CONCEPTUAL PROVISIONS FOR ENSURING BALANCED DEVELOPMENT OF THE REGIONAL LABOR MARKET - GRES, Bogdan (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The study focuses on the issues of forming and implementing an effective labor market development policy in the region. The conceptual basis and basic vector of such a policy is the formation of a structurally balanced labor market development. That is why the purpose of the study was to develop conceptual provisions to ensure the balanced development of the labor market in the region. As a result of the generalization of the essential and meaningful characteristics of the functioning and development of the labor market in the region, it was established that in the process of its regulation, not only direct tasks are implemented to provide the population with employment and decent wages, but also solves a whole complex of significant socio-economic problems for the region. It is emphasized that the integrity of the interaction of structural elements of the labor market (subjects, market mechanism, social and labor relations, market infrastructure) affects the achievement of balance in the development of the labor market. The main elements that determine the effectiveness of the balanced development of the labor market of the region are identified, namely, de-shadowing of social and labor relations in local and rural areas, expansion of the information base of institutional support for the labor market, introduction of digital technologies into the regional economy, increase in the level of youth employment, formation of intellectual capital, creation of conditions for self-employment of the population, ensuring gender equality, introduction of innovations into business, coordination of efforts and interaction of all parties to social and labor relations (state, employer, employee). Institutional support for the balanced development of the labor market in the region should be understood as a set of formal and informal institutions, the presence, interaction and cooperation of which form socio-economic instruments and institutional mechanisms that influence the nature, intensity and quality of development of the regional labor market, regulate and support the action of its elements, modify the structure, satisfy the interests of its subjects, and guide the processes of influence of social and labor relations on the development of the economy of regions and communities.